Numerical study of sweep angle effects of the control fin in supercavitating flow - Van-Duyen Pham; Byoung-Kwon Ahn (Engineering Applications of Computational Fluid Mechanics)
In this study, we numerically investigated the effects of sweep angle variations (Λ = 0°, 30°, 60°) of the control fin in supercavitating flow. Simulations were conducted using an unsteady Reynolds-averaged Navier-Stokes (URANS) approach coupled with the k–ϵ turbulence model. The influence of sweep angles on the supercavity geometry, hydrodynamic forces, and internal supercavitating flow was analyzed. Under fixed flow conditions, larger sweep angles resulted in smaller supercavity separations. The sweep angle significantly affected the fins’ hydrodynamic characteristics. Compared to the unswept fin, swept fins experienced reduced drag forces, with a maximum reduction of 48% observed at a sweep angle of 60°. In contrast, the unswept fin generated higher lift forces, showing increases of 50% and 23% compared to sweep angles of 60° and 30°, respectively. Additionally, swept fins exhibited smaller fluctuations in hydrodynamic forces than their unswept fins. Observations of the internal supercavitating flow revealed that larger sweep angles reduced the v-velocity component while increasing the w-velocity component in the wake region of the fin. Moreover, the unswept fin induced a greater volume of water inside the supercavity, which decreased with increasing sweep angles. Higher static pressure was observed in both the upstream and downstream regions of the fin as the sweep angle decreased. The insights from this study provide valuable guidance for designing control systems with optimal sweep angles for supercavitating vehicles, addressing a previously unexplored area of research.